Moral Intelligence and Academic Performance of Secondary School Students - Anito, Henok Daniel (Technium Social Sciences Journal, 2024)
This study investigated the relationship between moral intelligence and academic performance among secondary school students. The sample consisted of 123 respondents from grades 9-12 in a private international school in Indonesia. The study followed a descriptive-correlational research design. Descriptive statistics showed that the respondents had a moderate level of moral competency. Pearson’s product-moment correlation analysis revealed a weak but statistically significant positive relationship between moral intelligence and academic performance. Simple linear regression analysis indicated that moral intelligence significantly predicted academic achievement among high school students. An independent samples t-test revealed a significant difference in moral intelligence between the genders, with female students having higher moral competency than male students. One-way analysis of variance (ANOVA) showed a significant difference in moral intelligence across grade levels but no significant difference across religious affiliation. Implications of the findings and recommendations for further research were stated.